Peran Pendidikan Gerakan Revolusi Mental Berbasis Keluarga dalam Kebudayaan Nusantara - Husni Mubarok; Ria Norfika Yuliandari; Dian Mustika Anggraini (JEID: Journal of Educational Integration and Development, 2021)
The character of nation that is firmly guided by religion and noble values ??continues to decline.The existence of a mental revolution changes the perspective, thoughts, attitudes and behavior that is oriented towards progress and modernity, thus making the nation able to compete with other nations in the world. Understanding the mental revolution movement is an obligation for every family member to introduce the spirit of revolution to change constructive thinking patterns and have a level of productivity in thinking and working for the progress of the nation. The role of parents as caregivers and educators for children must have a balanced attitude in caring for and educating children. This research use library research with a qualitative approach. The research method used is content analysis. The results of this study discuss about the mental revolution, cultural education in the family and educational theory approaches.